2010
DOI: 10.4314/ijbcs.v3i6.53147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de la toxicité d’un extrait aqueux de <i>Sacoglottis gabonensis</i> (Baille) Urban (Humiriaceae) chez les rongeurs, une plante utilisée dans le traitement de l’ulcère de Buruli en Côte d’Ivoire

Abstract: RESUMESacoglottis gabonensis est une plante médicinale qui est utilisée dans le traitement traditionnel de l'ulcère de Buruli en Côte d'Ivoire. En vue d'établir l'innocuité de ce traitement, des tests de toxicité aiguë et subaiguë ont été réalisés. A cet effet, la DL 50 a été déterminée chez la souris, ainsi que les paramètres hématologiques et biochimiques après administration répétée des doses de 3,5 ; 35 et 350 mg/kg de pc de l'extrait aqueux de Sacoglottis gabonensis à des rats pendant 28 jours. La DL 50 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
6
1
4
Order By: Relevance
“…These results are in part similar and contrary to those of [15] and [16] which showed that the total aqueous extract of Sacoglottis gabonensis does not cause changes in the erythrocyte and leukocyte lines. Indeed [15], studying the influence of Sacoglottis gabonensis on the side effects of 2,4-dinitrophenylhydrazine on blood and cell metabolism, showed that administration of Sacoglottis gabonensis to rats did not alter the levels of red globules, hemoglobin, hematocrit, white blood cells, lymphocytes, neutrophils and monocytes.…”
Section: Hematological and Biochemical Examinationscontrasting
confidence: 56%
“…These results are in part similar and contrary to those of [15] and [16] which showed that the total aqueous extract of Sacoglottis gabonensis does not cause changes in the erythrocyte and leukocyte lines. Indeed [15], studying the influence of Sacoglottis gabonensis on the side effects of 2,4-dinitrophenylhydrazine on blood and cell metabolism, showed that administration of Sacoglottis gabonensis to rats did not alter the levels of red globules, hemoglobin, hematocrit, white blood cells, lymphocytes, neutrophils and monocytes.…”
Section: Hematological and Biochemical Examinationscontrasting
confidence: 56%
“…gabonensis is a tropical rain forest tree used in traditional medicine to treat BU. The acute and subacute toxicity studies of the aqueous extract of this plant showed a LD 50 value of 5000 mg/kg in mice per os whereas a 28 day administration of up to 350 mg/kg/day did not significantly influence haematological and biochemical parameters (Kone et al, 2009). Its aqueous extract showed promising activity against M. ulcerans in vitro (MIC¼780 mg/mL) (Kone et al, 2007) (Table 2).…”
Section: Sacoglottis Gabonensis (Baill) Urbmentioning
confidence: 89%
“…Extraction methods generally mimic herbal practitioners' approach to prepare decoctions or infusions using mainly water and palm wine (Yemoa et al, 2014(Yemoa et al, , 2011Addo et al, 2007;Kone et al, 2007Kone et al, , 2009. Other extraction procedures include the use of ethanol or organic solvents of increasing polarity (hexane, dichloromethane, ethyl acetate and water) to partition plant materials.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Researchers showed the antimycobacterial activity on the in vitro growth of Mycobacterium ulcerans from the total aqueous extract of the stem bark of S. gabonensis (ETASg) (Koné et al, 2007). In addition, acute and subacute oral toxicity tests performed in mice and rats, respectively, have shown that ETASg has an LD50 greater than 5000 mg/kg b. w. These tests also showed that it preserves the integrity of the liver, kidney and heart tissue in rats during 28 days of administration (Koné et al, 2009). In order therefore to guarantee its safety over a long period of use and recommend it as an alternative means in the management of Buruli ulcer in Côte d'Ivoire, this work aims at elucidating the toxicity effects of ETASg on rats' liver, kidneys and heart tissues for 90 days.…”
Section: Introductionmentioning
confidence: 93%
“…The total aqueous extract of S. gabonensis stem barks (ETASg) was obtained according to the method described by some authors (Koné et al, 2009). The fresh stem barks of S gabonensis harvested were carefully cleaned and then dried in Laboratory for three weeks at room temperature of 25 ± 2°C.…”
Section: Preparation Of the Stem Barks Total Aqueous Extract Of Sacogmentioning
confidence: 99%